Voz, performance e subversão: um estudo do narrador em “Kadosh”, de Hilda Hilst - Vieira, Maria Andrade (2019)
This dissertation proposes to investigate the way through which the voice of the narrator in the short story "Kadosh" (1973) by Hilda Hilst is constituted. The research aims at comparing Kadosh's peregrination to the aesthetics chosen by the author, including its hybridity in terms of the literary genres, the traits imprinted in the body of the text, as well as how the poetic language demands and promotes a place of otherness. Our research is based on the hypothesis that the voice of the narrator in Hilst represents the poetic undertaking, as a symbolic place created in order to generate a relationship of otherness with the reader through a performance writing. As such, we investigate, through a qualitative and descriptive research, the main characteristics of Hilda Hilst's creation of a poetic voice, considering an attentive reading of her published works, from the time of her debut as a poet to the constitution of this corpus, which unveils the concepts of performance and corporeality of the text as our theoretical cornerstone. As such, we have used the concept of voice by Massaud Moisés and Paul Zumthor; of performance by Richard Schechner, Renato Cohen and Paul Zumthor; of rhythm, image and language by Octavio Paz and Gaston Bachelard and Alberto Manguel's considerations (2018), Roland Barthes (2010) and Wolfgang Iser (1999) in terms of the relationship between the act of reading and the reader. We also use the concept of corporeality from the studies by George Bataille (2017) and Michel Collot (2004). In this research, we have found traits imprinted in the body of the text that create an experience in a way that transcend what the theory defines as performance: it is not a voice alone that performs in this corpus, but the text itself, in a structural aesthetics that communicates as the page turns into a stage and the words themselves come to life